Form Making of Advertising Structures Subject to TheCultural Perception Characteristics of The Ambient UrbanEnvironment; 8th World Conference on Educational Sciences (WCES-2016), 04-06 February 2016, Madrid, Spain - Khmelevsky Yu. P. Yury Petrovich (2016, 2016)
Title screen